Exploring the Islamic perspective on tissue engineering principles and practice - Sha'ban, Munirah; Zainuddin, Zainul Ibrahim; Abdul Rahman, Rozlin; Mohamad, Mohd Yusof; Mohamad Syukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin (Kolej Islam Darul Ridzuan, Perak, 2014)
Tissue engineering is related to the replacement, restoration, repair and/or regeneration of tissues/organs that are tailored to the needs of the individual patient. The potential applications of tissue engineering are being unveiled with much hype and expectations among the scientists and the public at large. The demand for engineered tissues may increase considerably, but the progress has been slow due to scientific and technical challenges that linked to moral, religious, philosophical, political and economic aspects. There are ongoing debates on certain aspects that seem to indicate that scientists maybe “playing God”. This article briefly analyses tissue engineering principles and the discourse surrounding it. Subsequently, the author briefly reflects on the Islamic perspectives, both for and against the technology. The discussions serve to provide a platform on how best to achieve a consensus that adequately deals with the scientific reality and the Islamic moral and legal jurisprudence that surrounds the technology.